Exploring 2d:4d finger length patterns as predictive biomarkers for knee osteoarthritis: Insights from a case-control study - Shaikh, Shazia Rahman; Bhatti, Urooj; Laghari, Mubina; Muhammad Ather (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the association and estimation of odds between second-digit-to-four-digit finger length patterns and knee osteoarthritis. Method: The case-control study was conducted at Liaquat University Hospital, Hyderabad, Pakistan, between December 2019 and December 2022, and comprised confirmed cases of knee osteoarthritis in group A and controls in group B. The second-digit-to-four-digit ratio was visually assessed. The participants placed their hands palm-down on a flat surface with fingers naturally extended and slightly separated. The ratio was determined by comparing the lengths of the index and ring fingers. Data was analysed using SPSS 23. Results: Of the 949 subjects, 190(20%) were in group A and 759(80%) in group B. Most group B controls (>50%) of both genders had equal index and ring finger lengths, while among group A cases, majority of males (>80%) and females (>70%) had longer ring fingers in both right and left hands, respectively. Significant association between hand finger patterns and knee osteoarthritis was found (p<0.001). Type III finger pattern on the left hand was independently associated with an increased risk of knee osteoarthritis (odds ratio: 3.17; 95% confidence interval: 1.31-7.69). Conclusion: Type III finger pattern of hand strongly correlated with an elevated risk of knee osteoarthritis. Key Words: Knee osteoarthritis, Finger pattern of hands, Type III finger pattern.